Enhancement of the Constrained Capacity Using the Dual-Alamouti Coding Over the PDL Fiber Channel - Zheng, Zhilong; Jin, Taowei; Wang, Rui; Zhao, Xue; Zhang, Jing; Qiu, Kun (Journal of lightwave technology, 2025)
Polarization dependent loss (PDL) remains one of major limitations for next-generation polarization-division-multiplexing (PDM) coherent optical transmission systems. Alamouti code has been proven to be polarization-independent and PDL-irrelevant thus can tolerate large PDL. However, Alamouti code is a half-rate code for a dual-polarization receiving system thus induces a half spectral efficiency loss. In this paper, we design a full-rate code defined as Dual-Alamouti code that consists of two Alamouti codes. The Dual-Alamouti code belongs to a more general theoretical model proposed by M. Shehadeh and F. R. Kschischang. They have proved that decoding a code with certain orthogonal property using an LMMSE-SIC scheme can achieve the capacity of a PDL-impaired channel. Based on the LMMSE-SIC scheme, we develop the DSP chain for the Dual-Alamouti code under a practical setup. We conduct 25-GBaud PDM-QPSK simulations and experiments to verify the performance of Dual-Alamouti coding and decoding scheme. The simulation and experiment results confirm that Dual-Alamouti coding provides stable performance against random incident state of polarization (SOP). A generalized mutual information (GMI) gain of 0.13 bits/sym over QPSK is observed when the optical signal-to-noise ratio is 10.5 dB and the PDL is 8 dB. Moreover, the proposed Dual-Alamouti code inherits the properties of traditional Alamouti code so that the transmission performance is robust to the joint effect of random polarization and PDL, which can reduce the signal-to-noise ratio (SNR) margin compared with traditional QPSK coded systems.